Which expression is equivalent to mc003-1.j pg? mc003-2.jp g mc003-3.j pg mc003-4.j pg mc003-5.jp g
answer is A
![Which expression is equivalent to mc0031j pg mc0032jp g mc0033j pg mc0034j pg mc0035jp ganswer is A class=](https://us-static.z-dn.net/files/de5/588e2829bce0854779bb9fbbc16177a9.png)
![Which expression is equivalent to mc0031j pg mc0032jp g mc0033j pg mc0034j pg mc0035jp ganswer is A class=](https://us-static.z-dn.net/files/ded/794e7fa661d46d7171bcff64584c0783.png)
Answer:
f(5)·g(5)
Step-by-step explanation:
fg(x) = f(x)·g(x), so
fg(5) = f(5)·g(5)
Answer:
Option A.
Step-by-step explanation:
The given expression is
[tex](fg)(5)[/tex]
According to the composition of functions, if f(x) and g(x) are two functions, then
[tex](fg)(x)=f(x)\cdot g(x)[/tex]
Substitute x=5 in the above formula, to find the expression which is equivalent to the given expression.
[tex](fg)(5)=f(5)\cdot g(5)[/tex]
Therefore, the correct option is A.